Mengapa Takut Ketinggalan Bisa Membuat Kita Kecanduan Game Online? - Anisa Resa Savitri; Aggio Malvino; Ayu Anjelina; Kania Jeanrita; Rani Sagita; Tesa Anggraini; Zuliana Wijaya (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to explore the relationship between FoMo (Fear of Missing Out) and online game addiction among students in West Sumatra aged 18-25 years. The method used is quantitative with purposive sampling technique and the research subjects amounted to 200 people. Data collection was carried out through a questionnaire that measured FoMo and online game addiction. The results showed that 97% of respondents were in the high online game addiction category, of which 35.5% were in the 21-year-old age group as the most vulnerable population. Data analysis using linear regression showed a positive correlation between FoMo and online game addiction (Pearson coefficient = 0.188, p = 0.004). The R square value of 0.035 indicates that FoMo contributed 3.5% to online game addiction, while 96.5% was influenced by other factors. These findings indicate that FoMo has a significant role in driving online game addiction behavior, although its contribution is relatively small.